(untitled) (Bioscience Journal, 2020)
The knowledge about growth and nutrient accumulation can help improve fertilizer efficiency in the production of jabuticaba seedlings, which is still carried out in an empirical way. This study aimed at determining the growth and macronutrient uptake in ‘Sabará’ jabuticaba genotypes grown in nutrient solution. The experiment was carried out in a completely randomized design in split plots, with four replications. In the main plots three jabuticaba genotypes (J001, J005 and J012) were cultivated in nutrient solution and six evaluation periods (at 60, 120, 180, 240, 300 and 360 days) in the sub-plots were evaluated. Plant height, root length, stem diameter, leaf area index and dry matter (root, stem and leaves) in each period were evaluated. The accumulation of macronutrients in different plant organs was determined, as well as the accumulation of nutrients as a function of time adjusted to the linear model. The results showed that the cultivation in nutrient solution was efficient in the production of Sabará jabuticabeira seedlings. There was no difference in macronutrient growth and absorption among jabuticaba genotypes grown in nutrient solution. ‘Sabará’ jabuticaba plants accumulated (in mg plant-1) 559 of N, 45 of P, 443 of K, 363 of Ca, 59 of Mg and 82 of S. The distribution of macronutrient accumulations in jabuticaba showed the following order: leaves > stem > roots.